Anti-acidogenic, anti-biofilm and slow release properties of Dodonaea viscosa var. angustifolia flavone stabilized polymeric nanoparticles. (January 2020) - Sebelemetja, Mpho; Moeno, Sharon; Patel, Mrudula
Graphical abstract: Highlights: PLGA-PEG/DVA flavone has anti- S. mutans activity. It also inhibited biofilm formation and acid production in S. mutans . Stabilised nanoparticles retained the flavone and released it slowly. The release of flavone was noted at physiological pH and at cariogenic pH. DVA derived flavone has anticariogenic potential. Abstract: Objective: Dental caries is caused by plaque associated oral bacteria including a pioneer species Streptococcus mutans. It has ability to form biofilm and produce acids in the oral cavity. Many oral hygiene products containing plant derived compounds have been investigated for their anti- S. mutans activity. Dodonaea viscosa var. angustifolia (DVA), has been found to have this property. However, beneficial concentrations are difficult to maintain in the oral cavity due to continual saliva flow which can be overcome using nanotechnology. The aim of this study was to investigate the anti-acidogenic, anti-biofilm and slow release properties of DVA derived flavone stabilized polymeric nanoparticles. Methods: Crude extract prepared from DVA leaves was fractionated to produce subfractions and the beneficial subfraction (F5.1) was obtained. Polymeric nanoparticles (PLGA-PEG) were prepared, stabilized with the DVA subfraction (F5.1/NPs) and characterized. Anti- S. mutans, anti-acidogenic and antibiofilm properties were determined. The subfraction release profile (substantivity) and cytotoxicity was determined. Results were analyzed using the Wilcoxon sum test (Mann-Whitney). Results: F5.1/NPs showed anti- S. mutans property (MIC 1.56 mg/ml). Subinhibitory concentrations of these nanoparticles significantly reduced the acid production in S. mutans (p < 0.01) and also reduced the biofilm formation by 92%. The retention and slow release of the beneficial compound was detected up to 12 h, reaching 0.1 mg/ml concentration at pH 7.4 after 4 h and at pH 5.5 after 5 h. IC50 of F5.1/NPs was 62.5 µg/ml. Conclusion: the DVA flavone containing nanoparticles showed anticariogenic activity with improved substantivity. Therefore, they have potential for use to control dental caries.